Law and Firms' Access to Finance - Beck, Thorsten (World Bank, Washington, DC, 2013)
Why does a country's legal origin influence its firms' access to finance? Using data from over 4,000 firms in 38 countries, the authors show that firms in countries with French legal origin face significantly higher obstacles in accessing external finance than firms in common law countries. Next, their results indicate that French legal origin countries tend to have (1) less adaptable legal systems, as defined by the degree to which case law and principles of equity rather than simply statutory law are accepted foundations of legal decisions, and (2) less politically independent judiciaries, as defined by the degree of tenure of supreme court judges and their jurisdiction over cases involving the government. Finally, the authors find that the adaptability of a country's legal system is more important for explaining the obstacles that firms face in contracting for external finance than the political independence of the judiciary. So, they distinguish among competing explanations of why law matters for financial development by empirically documenting the links running from international differences in legal origin to the operation of the financial system at the firm level.